2021
DOI: 10.3390/ijerph18157908
|View full text |Cite
|
Sign up to set email alerts
|

The Physical Burden of Water Carrying and Women’s Psychosocial Well-Being: Evidence from Rural Nepal

Abstract: Many women in low-income countries carry heavy loads of drinking water for their families in difficult terrain. This can adversely affect their health and well-being. The present study is the first to investigate the physical burden of water carrying and women’s psychosocial well-being, and how this relationship is moderated by environmental and health conditions. Trained local interviewers conducted interviews with 1001 women across five rural communities in Nepal. In addition, objective measurement was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 45 publications
1
7
0
2
Order By: Relevance
“…This finding aligns with previous systematic reviews, which have found a lack of WaSH-related water-borne disease studies among adult populations; most focus on children (Pouramin et al, 2020). As drinking water is a heavily gendered issue that disproportionately impacts women and is a known cause of many parasitic, infectious, and diarrheal diseases, we recommend future studies also include adult populations and disaggregate data by gender when evaluating water-related disease incidence (Mourad et al, 2019;Hunter et al, 2001;Beer et al, 2015;Tomberge et al, 2021;Graham et al, 2016). Furthermore, it is important to note the lack of research regarding the impact of water-related parasitic, infectious, and diarrheal diseases on pregnant women and newborns.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This finding aligns with previous systematic reviews, which have found a lack of WaSH-related water-borne disease studies among adult populations; most focus on children (Pouramin et al, 2020). As drinking water is a heavily gendered issue that disproportionately impacts women and is a known cause of many parasitic, infectious, and diarrheal diseases, we recommend future studies also include adult populations and disaggregate data by gender when evaluating water-related disease incidence (Mourad et al, 2019;Hunter et al, 2001;Beer et al, 2015;Tomberge et al, 2021;Graham et al, 2016). Furthermore, it is important to note the lack of research regarding the impact of water-related parasitic, infectious, and diarrheal diseases on pregnant women and newborns.…”
Section: Discussionsupporting
confidence: 87%
“…Inadequate access to WaSH services is responsible for 9.1% of the global disease burden and 6.3% of all deaths worldwide (Prüss-Üstün et al, 2008). Additionally, barriers to safe drinking water often lead to various negative health outcomes such as diarrhea, cholera, trachoma, typhoid, shigellosis, and malaria (Beer et al, 2015;Bisung and Elliott, 2017;Hunter et al, 2010;Moura et al, 2019;Mourad et al, 2019;Sengupta, 2013;Tomberge et al, 2021). A global study in 2014 of 145 countries concluded that WaSH-related diarrheal deaths accounted for 1.5% of the total disease burden, 58% of all diarrheal diseases, and 9% of all deaths for children younger than 5 years old (Liu et al, 2012;Prüss-Ustün et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study was conducted in the difficult terrain of the Nepalese hills where almost half of the women had to carry containers filled with water uphill or downhill. Nevertheless, the topography was not identified as a significant risk factor for water carrying related physical health outcomes among women in the reproductive age, although it was significantly related to higher emotional distress [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the responsibility for ensuring a sufficient supply of water to meet daily household demand lies mostly on women’s shoulders, access to water that is a distance away results in a considerable burden of time and energy for women who carry the water home [ 7 , 8 ]. This work is directly linked to women’s health because it can lead to musculoskeletal pain, fatigue, and emotional stress [ 9 , 10 ]. Geere et al conducted a systematic review of 42 studies on the association between water carrying and health and found moderate quantitative and strong qualitative evidence that water carrying is associated with musculoskeletal pain, fatigue, perinatal health problems, and violence against vulnerable people.…”
Section: Introductionmentioning
confidence: 99%